I hovedet på en læser: Et forsøg på at forstå lydbogslæseren - Pennlert, Julia (Passage - Tidsskrift for litteratur og kritik, 2020)
Reading has historically been framed both as a social and as an individual activity. During the last decade, the development of digital technologies has shed a new light on reading as a social practice, where readers can meet and share their reading experiences with others online. This article aims to chart the social traces that digital audiobook readers leave behind by analyzing reviews posted in the streaming service Storytel’s app and discussions between readers published in the Swedish Facebook-group “Talk about Audiobooks”. Drawing on theoretical insights from i.a. Elizabeth Long and Rita Felski, the article characterizes audiobook-users’ modes of reading and using literature.